The Influence of Time Equilibration to The Quality of The Swamp Buffalo (Bubalus bubalis) Cement After Thawing - Gian Dina Febriani; Hamdan Hamdan; Juli Melia (Universitas Syiah Kuala, 2014)
This research aims to know the influence of the equilibration to the quality of the swamp buffalo (Bubalus bubalis) cement after thawing including: motility, and percentage of live spermatozoa. This research used the fresh cement from a 4 years old water buffalo was collected using an artificial vagina,and evaluation cement for macroscopic and microskopic to see if cement was worthy or not worthy to frozen. Good quality cement was diluted by adding Andromed, then semen were incorporated into the straw using the machine filling sealing followed by equilibrated with 3 treatment groups. Group I (n = 3 straw) with equilibration time of 3 hours, the Group II (n = 3 straw) with a time of equilibration was 5 hours, and group III (n = 3 straw) with equilibration a time of 7 hours. After equilibrated, straw frozen and stored in liquid N2 (BIBD Tuah Sakato procedures). The results show that the length of time the real equilibration effect (P 0.05) on the motility and percentage life of swamp buffalo spermatozoa. Equilibration 5 hours of time differs markedly with equilibration time 3 and 7 hours, motility, and percentage of live spermatozoa (44.15±1.70; 46.50±1.36 vs 14,55±1,58; 1.42±37.38 vs. 15.37±1.58; and 37.50±1.25). In conclusion, equilibration time is showed on the cement of swmp buffalo after 5 hours thawing.Key words: equilibration, swamp buffalo, thawing